Effects of Ankaferd BloodStopper on dermal healing in diabetic rats - (:unkn) unknown (My University, 2017)
0

Background/aim: Diabetes mellitus inhibits wound-induced angiogenesis, impairs the wound healing process, and leads to the development of chronic wounds. Ankaferd BloodStopper (ABS) is a new and promising local haemostatic agent. Although the mechanism of ABS-mediated haemostasis is well established, little is known about the associated histological and biochemical tissue reactions. The aim of this study was to evaluate the effects of this new-generation local haemostatic agent on short-term soft-tissue healing in streptozotocin (STZ)-treated rats. Materials and methods: The 24 Wistar albino rats used in this study were divided into STZ-treated (STZ, n = 12) and nontreated groups (control, n = 12). Four days prior to surgery, rats in the STZ group were subcutaneously administered 60 mg/kg STZ intraperitoneally, while rats in the control group were administered 1 mL saline/kg. An incision was made in the dorsal dermal tissue of all rats, and either ABS or no haemostatic agent (NHAA) was applied to the wound before suturing. All of the rats were euthanised on postoperative day 4. Blood and skin samples were evaluated biochemically and histologically. Results: The results showed that STZ treatment impaired soft-tissue healing, assessed by measuring glutathione and lipid peroxidation levels. Moreover, while good histological results were obtained in the control group treated with ABS, there were fewer benefits in the STZ-treated group. Conclusion: ABS s benefits in the control group seemed to lose their effectiveness under STZ medication.
Keywords: Cerrahi